Infância e cidadania: uma análise da participação de crianças em políticas para a Primeira Infância no Distrito Federal: Childhood and Citizenship: an analysis of children’s participation in Early Childhood Policies in the Federal District - Costa, Karina Mel; Morais, Lucimara Gomes Oliveira de; Pinto, Viviane Fernandes Faria (Revista Cocar, 2025)
O artigo analisa a participação infantil em duas ações governamentais do Distrito Federal: a elaboração do Plano Distrital pela Primeira Infância (PDPI) e o Programa Plenarinha, da Secretaria de Estado de Educação do Distrito Federal (SEEDF). A metodologia adotada tem orientação qualitativa, e a aproximação com o objeto ocorreu por meio de análise bibliográfica e documental. Os resultados indicam que, embora a elaboração do Plano e da Plenarinha se fundamente na defesa da participação das crianças, ainda persistem desafios para o envolvimento efetivo delas nos processos decisórios. Além disso, tanto o PDPI quanto a Plenarinha apresentaram baixos índices de participação infantil em relação ao total de crianças matriculadas nas instituições educativas do Distrito Federal, o que evidencia desafios persistentes para a efetivação da participação como direito. Palavras-chave: Plano Distrital pela Primeira Infância; Plenarinha; Direito à participação. Abstract The article analyzes children's participation in two government actions in the Federal District: the construction of the District Plan for Early Childhood (PDPI) and the Plenarinha Program, an event aimed at promoting children-led projects, both from the Federal District State Department of Education (SEEDF). The methodology adopted is qualitative in approach, and the subject was examined through bibliographic and documentary analysis. The results indicate that, although the Plan and Plenarinha are based on promoting children's participation, challenges persist in terms of their effective involvement in decision-making processes. Moreover, both the Federal District’s Plan for Early Childhood and the Plenarinha exhibited low children participation rates in comparison to the number of children enrolled in the Federal District’s schools, which shows persistent challenges to the effective realization of participation as a right. Keywords: Federal District’s Plan for Early Childhood; Plenarinha; Right to participation.